Prioritising the most needed paediatric antiretroviral formulations: the PADO4 list. Issue 9 (September 2019) - Penazzato, Martina; Townsend, Claire L; Rakhmanina, Natella; Cheng, Yao; Archary, Moherndran; Cressey, Tim R; Kim, Maria H; Musiime, Victor; Turkova, Anna; Ruel, Theodore D; Rabie, Helena; Sugandhi, Nandita; et al.
Summary: Despite considerable progress in paediatric HIV treatment and timely revision of global policies recommending the use of more effective and tolerable antiretroviral regimens, optimal antiretroviral formulations for infants, children, and adolescents remain limited. The Paediatric Antiretroviral Drug Optimization group reviews medium-term and long-term priorities for antiretroviral drug development to guide industry and other stakeholders on formulations most needed for low-income and middle-income countries. The group convened in December, 2018, to assess progress since the previous meeting and update the list of priority formulations. Issues relating to drug optimisation for neonatal prophylaxis and paediatric treatment, and those relating to the investigation of novel antiretrovirals in adolescents and pregnant and lactating women were also discussed. Continued focus on identifying, prioritising, and providing access to optimal antiretroviral formulations suitable for infants, children, and adolescents is key to ensuring that global HIV treatment targets can be met.